Slower gait, slower information processing and smaller prefrontal area in older adults. - Rosano, Caterina; Studenski, Stephanie A; Aizenstein, Howard J; Boudreau, Robert M; Longstreth, William T; Newman, Anne B (Age Ageing, 2012)
BACKGROUND: Slower gait in older adults is related to smaller volume of the prefrontal area (PFAv). The pathways underlying this association have not yet been explored. Understanding slowing gait could help improve function in older age. We examine whether the association between smaller PFAv and slower gait is explained by lower performance on numerous neuropsychological tests. HYPOTHESIS: We hypothesise that slower information processing explains this association, while tests of language or memory will not. METHODS: Data on brain imaging, neuropsychological tests (information processing speed, visuospatial attention, memory, language, mood) and time to walk 15 feet were obtained in 214 adults (73.3 years, 62% women) free from stroke and dementia. Covariates included central (white matter hyperintensities, vision) and peripheral contributors of gait (vibration sense, muscle strength, arthritis, body mass index), demographics (age, race, gender, education), as well as markers of prevalent vascular diseases (cardiovascular disease, diabetes and ankle arm index). RESULTS: In linear regression models, smaller PFAv was associated with slower time to walk independent of covariates. This association was no longer significant after adding information processing speed to the model. None of the other neuropsychological tests significantly attenuated this association. CONCLUSIONS: We conclude that smaller PFAv may contribute to slower gait through slower information processing. Future longitudinal studies are warranted to examine the casual relationship between focal brain atrophy with slowing in information processing and gait.
Keywords: Affect; Aged; Aged, 80 and over; Aging; Attention; Body Mass Index; Cross-Sectional Studies; Female; Gait Disorders, Neurologic; Geriatric Assessment; Humans; Male; Memory; Mental Disorders; Mental Processes; Muscle Strength; Neuroimaging; Neuropsychological Tests; Prefrontal Cortex; Prevalence; Walking